Pilihan Judul Tesis (Kajian Deskripsi Tesis Pada Universitas XYZ Di Jakarta) - Suparman Ibrahim Abdullah; Heru Sriyono; Sara Sahrazad (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
This study discusses the difference between thesis and dissertation according to various sources. Then how to determine a good title, especially for a thesis title. Furthermore, based on a sample of 1052 titles in a graduate program in Jakarta XYZ studied with methods of descriptive findings indicate that the initial tendency to use the word, then the dependent variable and the independent variables are in use. Besides, there is a tendency that is less varied methodologies, and new allegations of an error derived sequentially. There are still relatively thin presence of plagiarism that marked the memorable quote rewrite its source in the bibliography. However, they all meet the weight requirements assessed as scientific papers thesis. Based on the interim findings made several suggestions for improvement in order to improve the quality of the content of the research on the above thesis.